2021
DOI: 10.3892/br.2021.1406
|View full text |Cite
|
Sign up to set email alerts
|

Association between clinicopathological features of breast cancer with adipocytokine levels and oxidative stress markers before and after chemotherapy

Abstract: Adipocytokines and markers of oxidative stress have been shown to exhibit potential for detection of advanced stage, HER2/neu status and lymph node metastases in patients with breast cancer, as well as in determining the efficiency of anti-cancer treatments. In the present study, blood concentrations of apelin (APLN), retinol-binding protein 4 (RBP4), 8-hydroxydeoxyguanosine (8-oxo-dG) and total antioxidant capacity (TAC) in women with breast cancer with different clinicopathological features were measured pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One of the best methods to assess oxidative stress is to study levels of 8-hydroxydeoxyguanosine (8-oxo-dG). Interestingly, several studies have observed that levels of 8-oxo-dG in urine or blood may be a useful biomarker of therapy response in cancer patients [ 87 , 88 , 89 ].…”
Section: Cancer-associated Alterationsmentioning
confidence: 99%
“…One of the best methods to assess oxidative stress is to study levels of 8-hydroxydeoxyguanosine (8-oxo-dG). Interestingly, several studies have observed that levels of 8-oxo-dG in urine or blood may be a useful biomarker of therapy response in cancer patients [ 87 , 88 , 89 ].…”
Section: Cancer-associated Alterationsmentioning
confidence: 99%
“…Eight studies examined the relationships between apelin concentration and BMI and/or other body composition measurements (Table 3). Of those eight studies, four [18,19,31,32] reported no relationships between BMI or adipose tissue content and apelin concentration, while the other four studies [21][22][23]26] showed various levels of significant relationships, such as a positive correlation between BMI and apelin in three studies. One of these four studies [26] showed reduced apelin levels after 12 months had decreased waist-hip ratios and lower fat mass.…”
Section: Demographic and Clinical Characteristics And Apelin Concentr...mentioning
confidence: 99%
“…APLN can also be used as an independent predictor of breast cancer and apelin level can indirectly reflect the patient's chemotherapy effect, which also shows the potential clinical utility of apelin. The tumor expression of apelin in BC is also related to adverse reactions to neoadjuvant chemotherapy (Grupińska et al, 2021). Apelin/APJ system can significantly reduce the therapeutic effect of VEGF inhibitors in patients with ovarian cancer.…”
Section: Role Of Apelin/apj System In Cancer Development and Progressionmentioning
confidence: 99%
“…Apelin/APJ system pay an essential role in the occurrence and development of various cancers, which is closely related to the high recurrence and mortality of multiple cancers, such as liver cancer (Hall et al, 2017), gastroesophageal cancer (GC; Diakowska et al, 2014), colon cancer (Picault et al, 2014), breast cancer, multiple myeloma (MM; Maden et al, 2016), glioblastoma (GBM; Aktan & Ozmen, 2019), renal cell carcinoma (RCC; H. P. Zhang, et al, 2017), oral squamous cell carcinoma (OSCC; Heo et al, 2012), endometrial cancer (Altinkaya et al, 2015), and lung cancer (Berta et al, 2010; De Munck et al, 2020). Furthermore, apelin/APJ system even affects the efficacy of some anticancer drugs, thereby affecting the efficacy of cancer treatment and the occurrence of poor prognosis (Y. Chen et al, 2021; Gourgue et al, 2021; Grupińska et al, 2021; D. Lv et al, 2021). These evidence indicated that apelin/APJ system plays an indispensable role in the cancer progression by influencing tumor microenvironment, angiogenesis, blood vessel density, cell migration and invasion, and cell apoptosis through multiple pathways (Baran et al, 2020; Masoumi et al, 2020; Masri et al, 2009; Podgórska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation